2017
DOI: 10.1016/j.thromres.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of tissue factor pathway inhibitor 2 in human placenta of preeclampsia

Abstract: Over-expression of TFPI-2 and aberrant promoter mythylation status presented in the PE placentas, suggesting that epigenetic mechanism might contribute to the pathogenesis of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…For example, Zhou et al found that TFPI2 expression caused impairment of invasion and proliferation, and induced apoptosis in BeWo and JEG3 cells. Xiao et al have also reported overexpression of TFPI2 and aberrant promoter methylation status presented in PE placentas, suggesting that an epigenetic mechanism might result in the pathogenesis of PE. However, the role of TFPI2 in the pathogenesis of PE is still unknown.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Zhou et al found that TFPI2 expression caused impairment of invasion and proliferation, and induced apoptosis in BeWo and JEG3 cells. Xiao et al have also reported overexpression of TFPI2 and aberrant promoter methylation status presented in PE placentas, suggesting that an epigenetic mechanism might result in the pathogenesis of PE. However, the role of TFPI2 in the pathogenesis of PE is still unknown.…”
Section: Discussionmentioning
confidence: 97%
“…Xu et al () indicated that MiR‐616‐3p upregulation stimulates cell proliferation and migration via targeting TFPI2 in PE. Xiao et al () reported that long noncoding RNA 00473 silences TFPI‐2 epigenetically by binding to lysine‐specific demethylase 1, promoting trophoblasts' invasion and migration, which are dysregulated in PE. High HIF‐1α and VEGF expression could be observed in placenta tissues of PE women (Ali et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF and hypoxia inducible factor (HIF)‐1α are involved in the pathophysiology of PE, and the HIF1α‐VEGF axis participates in the regulation of tight junction that sustains normal placental barrier integrity (Ali, Salih, Elhassan, Mohmmed, & Adam, ; Zhang et al, ). Suppressor gene tissue factor pathway inhibitor 2 (TFPI‐2) is indicated to be aberrantly expressed in the placenta of PE and might contribute to the pathogenesis of PE (Xiao et al, ), meanwhile is supposed to be potential therapeutic target of PE (Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the TFPI2 promoter contains some of the CpG islands participating in transcriptional silencing [ [31] , [32] , [33] ]. To determine whether PARP1 mediates hyperglycemia-induced TFPI2 promoter DNA methylation thus decreasing TFPI2 activity, the methylation levels of CpG islands in the TFPI2 promoter were examined using the MassARRAY assay (Sequenom).…”
Section: Resultsmentioning
confidence: 99%